Clinical Characteristics and Genetic Analysis of a Family With Birt-Hogg-Dubé Syndrome and Congenital Contractural Arachnodactyly - Qiu, Jiayong; Lou, Yao; Zhu, Yingwei; Wang, Min; Peng, Huifang; Hao, Yingying; Jiang, Hongwei; Mao, Yimin (Frontiers in Genetics, 2022)
Abstract Background Birt-Hogg-Dubé Syndrome (BHD syndrome) and congenital contractural arachnodactyly (CCA) or Beals Hecht Syndrome (BHS) are clinically rare autosomal dominant genetic diseases. In this study, we find an extremely rare family with BHD Syndrome with CCA. Objective To investigate the clinical and genetic variation characteristics of a family with BHD Syndrome with CCA. Methods The patient was examined for chest Computed Tomography (CT), abdominal and heart color ultrasound, rheumatism immune-related indexes, and hand Direct Digital Radiography (DR), and Whole Exome Sequencing (WES) was performed on family members. Results The proband, male, developed symptoms of chest tightness and shortness of breath, accompanied by irritant cough 2 years ago, and then repeated spontaneous pneumothorax four times. Chest CT showed: spontaneous pneumothorax on the right side, emphysema in both lungs, and bullae in both lungs. No manifestations of kidney tumors and skin lesions. His son had a history of pulmonary bullobes and occurred spontaneous pneumothorax twice. He, his mother, and his son were all born with a hand deformity. Sequencing results showed that both the proband and his son were folliculin (FLCN) gene c.1015C>T（p.Gln339Ter） heterozygous variation, Fibrillin 2 gene (FBN2) gene c.3485G>A（p.Cys1162Tyr） heterozygous variation, associated with BHD syndrome and CCA. Conclusion For patients with chest tightness, shortness of breath, recurrent spontaneous pneumothorax, and congenital hand deformity without inducement, genetic testing should be carried out as soon as possible to make a clear diagnosis, which can guide treatment and genetic counseling.